Approximate Solution of Inverse Problem for Elliptic Equation with Overdetermination - Charyyar Ashyralyyev; Mutlu Dedeturk (Abstract and Applied Analysis)
A finite difference method for the approximate solution of the inverse problem for the multidimensional elliptic equation with overdetermination is applied. Stability and coercive stability estimates of the first and second orders of accuracy difference schemes for this problem are established. The algorithm for approximate solution is tested in a two-dimensional inverse problem.